SECONDARY SCHOOL TEACHER OBSERVATION ON THEIR APPLICATION OF DISTRIBUTED LEADERSHIP STYLE - Khmaladze, Sophio (PROFESSIONAL STUDIES: Theory And Practice, 2024)
Distributed leadership in secondary education is a leadership style in which all educational personnel at school is involved in the improvement of teaching and learning. Its application corresponds to the contemporary requirements of education organization/management. However, in countries building democracy, such as Georgia, distributed leadership is not sufficiently applied and its application and impacts have not been studied. The paper presents the results of an experimental study at two schools – the experimental one, where teachers were trained to be involved in distributed leadership, and the control one, where no such training was organized. Then for one semester, the teachers in both schools did self-observation and were observed by three observers to see whether they differed in the application of distributed leadership. The results confirmed that a statistically significant improvement in distributed leadership application took place at the experimental school, while no such improvement occurred at the control school. A recommendation is given that for teachers insufficiently aware of distributed leadership style training concerning its clear definition, benefits, and challenges is necessary.